The problem of inequalities in health on the basis of organization and financing of obstetric care in the Masovian and Subcarpathian voivodeships - Raba, Grzegorz; Obłoza, Beata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
Introduction: The phenomenon of inequalities in health is a major concern of the population of Poland. To date, no single pattern of financing health care has been developed in Poland. Objective: 1. Evaluation of the organization of care for women at birth and the neonate in the Masovian and Subcarpathian voivodeships. 2. Comparison of the administered funds for both voivodeships to provide obstetric and neonatal care. 3. Determination of the consistency of the system of care including epidemiological and demographic data of the inhabitants of both voivodeships. Material and method: Data concerning the demographics of the population of the Masovian and Subcarpathian voivodeships was obtained from the official GUS (Central Statistical Office of Poland) website: http://stat.gov.pl/. The aggregate values of contracts in the years 2010 – 2014 in the Masovian and Subcarpathian voivodeships were obtained from the official NFZ (the Polish National Health Fund) website at: http://www.nfz.gov.pl. Conclusions: 1. The values of contracts attributable to a single obstetric bed are comparable only in I reference level centres. II and III reference level centres receive higher funds in the Masovian voivodeship. 2. In the Subcarpathian voivodeship there is a smaller number of highly specialized neonatal care stations in III reference level centres per number of inhabitants and the number of births. 3. Higher values of contracts concluded in the Masovian voivodeship with II and III reference level centres do not correlate with the decrease in perinatal mortality rate and the preterm birth rate, registered in this voivodeship.

Wstęp: Zjawisko nierówności w zdrowiu jest poważnym problemem ludności Polski. Do chwili obecnej nie opracowano w Polsce ujednoliconego wzorca finansowania służby zdrowia. Cel: 1. Ocena organizacji opieki nad kobietą rodzącą i noworodkiem w województwach mazowieckim i podkarpackim. 2. Porównanie wielkości środków finansowych dysponowanych do obu województw w celu zapewnienia opieki położniczo-noworodkowej. 3. Określenie spójności systemu opieki z uwzględnieniem danych epidemiologicznych i demograficznych mieszkańców w obu województwach. Materiał i metoda: Dane dotyczące demografii ludności zamieszkującej województwa mazowieckie i podkarpackie pozyskano z oficjalnej strony internetowej GUS: http://stat.gov.pl/. Sumaryczne kwoty kontraktów w latach 2010–2014 w województwach mazowieckim i podkarpackim, uzyskano z oficjalnej strony NFZ pod adresem: http://www.nfz.gov.pl. Wyniki, wnioski: 1. Wartości zawieranych kontraktów przypadające na każde łóżko położnicze są porównywalne jedynie w ośrodkach o I stopniu referencji. Ośrodki II oraz III stopnia referencji uzyskują wyższe finansowanie w województwie mazowieckim.2. W województwie podkarpackim stwierdza się mniejszą liczbę wysokospecjalistycznych stanowisk opieki neonatologicznej w ramach ośrodków o III stopniu referencyjnym, przypadających na liczbę mieszkańców oraz liczbę urodzeń. 3.Wyższe wartości kontraktów zawieranych na terenie województwa mazowieckiego z ośrodkami o II i III stopniu referencyjnym nie korelują z obniżeniem wskaźnika umieralności okołoporodowej noworodków oraz odsetkiem porodów przedwczesnych, rejestrowanych w tym województwie.
Problem nierówności w zdrowiu na przykładzie organizacji i finansowania opieki położniczej w województwach mazowieckim i podkarpackim
Keywords: financing of the medical care system; public health; health inequalities; zdrowie publiczne; finansowanie opieki medycznej; nierówności w zdrowiu